Work Environment and Academic Staff Performance in Tertiary Institutions in Nigeria - Sani Kasimu; Matakhitswen, Kefas; Emmanuel, Danladi (International Journal of Applied and Advanced Multidisciplinary Research, 2024)
This study is a review study and it was aimed to examine the impact of work environment on academic staff performance in tertiary institutions in Nigeria. Depending on secondary data that were systematically collected from print and online publications. The results collected indicated that the work environment of tertiary institutions influences academic staff job performance. The paper concluded that a good and conducive working environment enhances the job performance of Academic Staff in tertiary institutions. Based on this, the paper suggested that the government and relevant stakeholders in the management of tertiary institutions in Nigeria should ensure that: a conducive work environment should be provided in all tertiary institutions across the country.